Fundamentals of biochemistry - U Satyanarayana; Chakrapani, U (Kolkata Books and Allied, 2019)
Chemical Constituents of life; Physiological Biochemistry; Metabolisms; Clinical Biochemistry and Nutrition; Molecular Biology and Biotechnology; Current Topics; Basics to learn Biochemistry.
Keywords: Biochemistry